From anti-social policy to generalised insecurity: The Greek crisis meets the decline of the European Social Model - Papadopoulos, Theo; Roumpakis, Antonios (Κοινωνική Πολιτική, 2017)
Our article examines key aspects of the Greek crisis and explores it under the light of the ongoing decline of the European Social Model. It is argued that the austerity measures implemented as conditions for receiving consecutive ‘bail-out’ loans have had, so far, a very negative impact upon the Greek economy, politics and society. Further, it is argued that labour market reforms underway inGreeceand the rest ofSouthern Europesignal some very worrying developments with respect to the social dimension of European integration. Indeed, especially in the area of collective agreements, when we view these reforms from a European perspective we can identify the rise of wage policy interventionism by the EU; a new process that ‘combines European requirements for national wage and labour market policies with the threat of economic sanctions’ (Busch et al (2013:8). In turn this signals the intensification of the (neo) liberalisation of the European Social Model and puts under severe doubt the prospects for a more socialEuropethat will prioritize social objectives and rights over economic freedoms.